Analysis of Factors Affecting the Work Discipline of Employees CV. Golden Seafresh Medan - Intan Permatasari Gojali; Ferry Hidayat (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of compensation, leadership and supervision on the work discipline of employees of CV. Golden Seafresh Medan. This type of research is explanatory research. The population in this study were all employees of CV. Golden Seafresh has 59 employees. The technique of determining the sample uses a saturated sample. In this study, the questionnaire will be distributed as measured by a Likert scale. Data analysis used multiple linear regression analysis and coefficient of determination as well as simultaneous and partial tests. The results showed that compensation, leadership, and supervision partially or simultaneously had a positive and significant effect on employee work discipline on CV. Golden Seafresh. Based on the results of this study, the implication for management is to be able to adjust compensation, leadership style and implementation of better supervision.